APPLICATION OF DEVELOPING CLOTHING RECOMMENDATION SYSTEM WITH ARTIFICIAL INTELLIGENCE TECHNIQUES - Özbek, Ahmet; Altuntaş, Volkan; Erdoğan, Naile (Chamber of Textile Engineers, 2024)
This study aims to develop a clothing recommendation application for users who possess a large number of clothes but have limited time due to their intense work tempo. This application aims to assist them in using their clothes effectively, reducing the time spent on selecting outfits, and dressing fashionably. In the process of developing this application, firstly, the criteria influencing the user’s clothing preferences were determined. Subsequently, a wardrobe dataset was created based on the established criteria. Following this, methods for suggesting clothes were explored. As a result of the research, it was decided to utilize association rule analysis, multidimensional clothing representation coding, and weighted L1 distance methods for clothing recommendation in this study. In the application phase, experiments were conducted using the dataset associated with the chosen methods. It has been determined that the application developed in this study gives successful results in suggesting clothes suitable for user preferences. © (2024), (Chamber of Textile Engineers). All rights reserved.
YAPAY ZEKA TEKNİKLERİ İLE GELİŞTİRİLEN GİYİM ÖNERİ SİSTEMİNİN UYGULANMASI
Keywords: Artificial Intelligence Techniques; Clothing; Giyim; Recommendation system; Selection Criteria; Seçim Kriterleri; Yapay Zeka Teknikleri; Öneri sistemi